(untitled) (Scientific journal of the Fergana State University, 2023)
This article touches upon the six types of the verbalizers of the conceptual macrosemantics of “intensification/deintensification” established for the first time in Modern English, Uzbek and Russian, which allowed to reveal the isomorphic and allomorphic features of the verbalizers and the factors preconditioning the latter.